Application of the methodology of service-learning for leadership training in the students of the specialist of elementary and Bilingual Intercultural Education at the National Santiago Antúnez de Mayolo Huaraz University - Cerna Ruiz, Liszeth (2016)
The present research has as objective general demonstrate the influence of the methodology of the learning service in the training of leadership of them students of the specialty of Primary and Education Bilingual Intercultural of it UNASAM.Applied an explanatory causal research and research design is quasi-experimental, where included a control group of the VI and VII cycle and an experimental group of the VIII and IX cycle of the mentioned specialist. The verification of the performance of the sample is collected by a tab of registration, questionnaires and the test of Likert allowing to evaluate the style of leadership of students and the application of the methodology of the learning service.The results of this research allowed to establish the influence of the methodology in the training of educator's leaders, proving the hypotheses raised as community service and development of skills for the exercise of leadership, the design of lifelong learning service in the decision-making process of the leadership for the decision-making and the strengthening of the relationships of leadership style consultative with the use of a communication system.